Safety and efficacy of the feed additive consisting of Clostridium butyricum FERM BP‐2789 (Miya‐Gold® S) for chickens for fattening, chickens reared for laying, turkeys for fattening, turkeys reared for breeding, minor avian species (excluding laying birds), piglets (suckling and weaned) and minor porcine species (Miyarisan Pharmaceutical Co. Ltd.). (8th March 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The feed additive under assessment (trade name: Miya‐Gold ® S) is based on viable spores of Clostridium butyricum FERM BP‐2789. It is authorised for use in minor avian species (excluding laying birds), weaned piglets and minor weaned porcine species, chickens reared for laying, turkeys for fattening and turkeys reared for breeding. This opinion concerns the request for renewal of the authorisation of Miya‐Gold ® S for the species/categories for which an authorisation exists, the use in chickens for fattening, for which the previous authorisation had expired, and the extension of use to suckling piglets and suckling minor porcine species. The applicant provided evidence that the additive currently in the market complies with the conditions of authorisation. There is no new evidence that would lead the Panel to reconsider previous conclusions that Miya‐Gold ® S remains safe for the animal species/categories, the consumer and the environment under the current and previously authorised conditions of use. This conclusion applies also to the new target species for which a request of use is made. Regarding the safety for the user, the Panel concluded that the additive is not irritant to skin and eyes and that sensitisation via respiratory route cannot be excluded. There is no need for assessing the efficacy of Miya‐Gold ® S in the context of the renewal of the authorisation in chickens reared for laying, turkeys for fattening and reared for breeding, minor avian species (excluding laying birds), weaned piglets and weaned minor porcine species. The additive has the potential to be efficacious in chickens for fattening, suckling piglets and suckling minor porcine species at the level of 2.5 × 10 8 CFU/kg complete feedingstuff. Miya‐Gold ® S is compatible with decoquinate, diclazuril, lasalocid, maduramicin ammonium, narasin, narasin/nicarbazin, monensin sodium, robenidine, salinomycin sodium and semduramicin.